Studi Penentuan Sebaran Kadar dan Estimasi Sumberdaya Nikel Laterit Pada PT X Kabupaten Luwu Timur - ma'rief, Al’Faizah; Aldiyansyah, Aldiyansyah (CV Insight Publisher, 2024)
I In nickel laterite mining, it is necessary to map grade distribution and estimates to be able to calculate resources before the mining process takes place. Resource estimation plays an important role in determining the quantity and quality of a deposit. On the basis of the foregoing, a study was conducted on exploration activities aimed at determining the amount of nickel laterite deposit resources. In this study, estimation of nickel laterite resources was carried out using the Inverse Distance Weighting (IDW) method. The purpose of this study was to determine the direction of distribution of grades and amount of nickel laterite deposit resources in the study area. This research was conducted using Microsoft Excel software, ArcGIS 10.8, surpac 6.5.1. Based on the results of the drilling database provided by PT X which totaled 20 drill points, the distribution of nickel laterite mineralization grades in the study area based on grade distribution maps, laterite nickel with grades <1 occupies the western and southeastern parts of the study area (green, yellow and red). , while the distribution of laterite nickel grades with grade values > 1 occupies the northeast, southwest and northwest (dark gray and purple colors). has nickel resources of 169.950 tons, with an average value of Ni content of 1,87% from the number of drill points of 20 with a spacing of 50 m.